GE_GERICHTE P/13870/2020 vom 9. Februar 2021 - GE Cour de justice (2021)
SÉQUESTRE(MESURE PROVISIONNELLE);TIERS;COMPÉTENCE RATIONE MATERIAE;CONFLIT DE COMPÉTENCES;TRIBUNAL PÉNAL FÉDÉRAL;ESCROQUERIE | CPP.263; CPP.28; DPA.25; LAMal.92